2012
DOI: 10.1007/s00402-012-1623-3
|View full text |Cite
|
Sign up to set email alerts
|

Core decompression and implantation of bone marrow mononuclear cells with porous hydroxylapatite composite filler for the treatment of osteonecrosis of the femoral head

Abstract: Both core decompression with or without implantation of BMMC are effective treatment for ONFH. However, core decompression with implantation of BMMCs and porous hydroxyapatite bone filler may be a more effective treatment for ONFH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
97
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 73 publications
(102 citation statements)
references
References 14 publications
3
97
0
Order By: Relevance
“…Liu et al (2013) found an improvement in both HHS and visual analog scale (VAS) in the cell therapy group compared to the controls at the end of follow-up (p < 0.0001 for both comparisons).…”
Section: Resultsmentioning
confidence: 95%
See 4 more Smart Citations
“…Liu et al (2013) found an improvement in both HHS and visual analog scale (VAS) in the cell therapy group compared to the controls at the end of follow-up (p < 0.0001 for both comparisons).…”
Section: Resultsmentioning
confidence: 95%
“…3 of the studies were randomized control trials (RCTs) (Sen et al 2012, Zhao et al 2012, Ma et al 2014), 1 was a prospective control study (Gangji et al 2011), and the remaining 3 were retrospective case-control studies (Yamasaki et al 2010, Lim et al 2013, Liu et al 2013). …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations